Is Endo the end-all? an empirical analysis of the relationship between labor productivity and short-term contracts in the Philippines - Mariano, Kelsey Savannah F. (School of Economics, University of the Philippines Diliman, 2018)
The administration of President Rodrigo Duterte has faced battle cry after battle cry to fully abolish labor_only contractualization, or endo in the Philippines. This paper aims to determine whether the use of temporary contracts or the employment of temporary workers, in the context of the Philippine labor market, is linked to higher labor productivity across various industries. We performed a multiple linear regression on the merged Labor Force Survey and Annual Survey of Philippine Business and Industries surveys. Results show that controlling for other explanatory variables, workers hired on a short_term basis are more productive than those hired permanently. We estimate that the difference in labor productivity, from employing temporary workers, range from 20.05 to 21.66 percent.